2013
DOI: 10.1371/journal.pone.0067579
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute Exercise on Prostate Cancer Cell Growth

Abstract: Physical activity is associated with reduced risk of several cancers, including aggressive prostate cancer. The mechanisms mediating the effects are not yet understood; among the candidates are modifications of endogenous hormone levels. Long-term exercise is known to reduce serum levels of growth stimulating hormones. In contrast, the endocrine effects of acute endurance exercise include increased levels of mitogenic factors such as GH and IGF-1. It can be speculated that the elevation of serum growth factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(108 citation statements)
references
References 34 publications
5
101
1
1
Order By: Relevance
“…The EGF interaction with its receptor leads to the activation of NADPH oxidase and the consequent production of ROS, which, in turn, stimulate the autophosphorylation of the membrane receptor and the induction of the signal cascade [72]. It is plausible that the post-exercise EGF reduction, an already reported finding [67], is finalized to facilitate defense mechanisms against oxidative stress. This hypothesis is supported by the proportional reduction in EGF levels in association with increasing BMI, concurrently with the exacerbation of oxidative stress levels in obese subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The EGF interaction with its receptor leads to the activation of NADPH oxidase and the consequent production of ROS, which, in turn, stimulate the autophosphorylation of the membrane receptor and the induction of the signal cascade [72]. It is plausible that the post-exercise EGF reduction, an already reported finding [67], is finalized to facilitate defense mechanisms against oxidative stress. This hypothesis is supported by the proportional reduction in EGF levels in association with increasing BMI, concurrently with the exacerbation of oxidative stress levels in obese subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Regular exercise has been shown to affect the IGF axis resulting in lower levels of serum insulin and IGF1 and increased levels of IGF-binding protein-1 in vivo with reduced proliferation and increased apoptosis of prostate tumor cells in vitro (21,22). A recent study also showed that serum extracted directly after strenuous exercise reduced the proliferation of prostate tumor cells in vitro, indicating an acute effect of physical activity on tumor growth (23). Altered levels of adipokines is an effect of obesity and also associated with tumor development (24).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, muscles were electrically stimulated to fatigue, and extracts from the exhausted muscles were injected directly into transplanted tumors in rats and shown to slow the growth of the tumors. 57,58 Using comparable conditioned media from cultured muscle cells for incubation of cancer cells in vitro, such media significantly reduces cancer cell growth. 55 The skeletal muscle is now recognized as an endocrine organ that secretes peptides during muscle contraction.…”
Section: Muscle-to-tumor Cross-talkmentioning
confidence: 99%